2013
DOI: 10.3389/fnins.2013.00059
|View full text |Cite
|
Sign up to set email alerts
|

Habitat-specific shaping of proliferation and neuronal differentiation in adult hippocampal neurogenesis of wild rodents

Abstract: Daily life of wild mammals is characterized by a multitude of attractive and aversive stimuli. The hippocampus processes complex polymodal information associated with such stimuli and mediates adequate behavioral responses. How newly generated hippocampal neurons in wild animals contribute to hippocampal function is still a subject of debate. Here, we test the relationship between adult hippocampal neurogenesis (AHN) and habitat types. To this end, we compare wild Muridae species of southern Africa [Namaqua ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
57
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(65 citation statements)
references
References 55 publications
6
57
2
Order By: Relevance
“…Within the surface-dwelling rodents, the South African species from an environmental challenging habitat form their own cluster. (Data from Amrein et al 2011Amrein et al , 2014Cavegn et al 2013. ) …”
Section: The Emergence Of Habitat-specific Patterns In Basal Neurogenmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the surface-dwelling rodents, the South African species from an environmental challenging habitat form their own cluster. (Data from Amrein et al 2011Amrein et al , 2014Cavegn et al 2013. ) …”
Section: The Emergence Of Habitat-specific Patterns In Basal Neurogenmentioning
confidence: 99%
“…Epp et al (2009) have used eye lens weights, assessed in both wild rats and laboratory conspecifics of known age, for age estimation. Barker et al (2003) and Cavegn et al (2013) combined lens weight with age-dependent structural changes in the number of adhesion lines in the circumferential lamellae of the femur. Even if it may not be possible to arrive at an exact absolute age that would allow direct comparison with laboratory-raised animals, it is at least possible to age wild animals relative to each other in a rather precise manner.…”
Section: Comparing the Age-dependent Regulation Of Hippocampal Neurogmentioning
confidence: 99%
“…Despite this ubiquity, however, neurogenesis in the adult hippocampus varies widely across species, with differences apparent in the rate of proliferation, survival, and neuronal maturation (for example, Cavegn et al 2013). The process appears absent in certain bat species (Amrein et al 2007), whereas especially high levels are found in rodents, especially rats (Amrein et al 2011).…”
mentioning
confidence: 99%
“…For example in chickadees, the results indicate that populations that live in harsher environmental conditions show increased neurogenesis (Chancellor et al, 2011). In rodents, a different approach has been followed where various species from diverse habitats were compared, and once again rodents species resident in more challenging environments show higher neurogenesis (Cavegn et al, 2013). Compared to these surface dwelling rodents, mole-rats have the lowest level of neurogenesis (Amrein et al, 2014, Penz et al, 2015.…”
Section: Neurogenesis In a Natural Rodent Populationmentioning
confidence: 99%
“…These differences appear to be largely dependent on hormonal variations (Marques et al, 2016). The precise functional significance of adult hippocampal neurogenesis is still a matter of debate, however evidence suggests that newly born neurons may have a more general function by contributing to behavioural flexibility in both wild and laboratory rodents (Garthe et al, 2009, Cavegn et al, 2013 by modulating the animal's reaction to novelty (van Dijk et al, 2015).…”
Section: Introductionmentioning
confidence: 99%